Municípios no federalismo fiscal da Constituição da República federativa do Brasil de 1988: uma análise das receitas tributárias do município de São José da Laje, Estado de Alagoas, competência 2012 a 2016. - Matias, Roseli da Silva (2018)
This paper begins a theoretical presentation on cooperative fiscal federalism. Afterwards, he presents the Municipalities in the Constitution of the Federative Republic of Brazil of 1988, without neglecting to discuss the complexities of the process of formation and extinction of municipal entities. The overwhelming emancipation of new municipalities, without criteria based on a study of financial viability, makes evident the fragility of the federative system. In contextualizing the importance of the municipal entities in the effectiveness of the Social State, it evaluates the system of revenue distribution for the Municipalities, presenting positive and negative aspects. A survey was carried out on the Municipality of São José da Laje, located in the State of Alagoas, relating the revenues of own taxes and those received from the Federal Government and the State of Alagoas, in financial years from 2012 to 2016, to determine the share of these revenues Intergovernmental Organizations in their Net Current Revenues. In the end, it presents the centralizing power of decisions and tax revenues on the part of the Union, reason for which it suffers the municipal autonomy. The conclusion, when discussing the entire structural division of labor, shows weaknesses in the federative fiscal cooperative system, which demand paradigm changes in the way the municipalities are treated.